Clinical Significance of Thyroid-Stimulating Hormone Receptor Gene Mutations and/or Sodium-Iodine Symporter Gene Overexpression in Indeterminate Thyroid Fine Needle Biopsies - Guan, Haixia; Matonis, Danielle; Toraldo, Gianluca; Lee, Stephanie L. (Frontiers in Endocrinology, 2018)
Objectives: To examine the prevalence of genetic alterations of thyroid-stimulating hormone receptor (TSHR) gene and sodium-iodine symporter (NIS) in a series of thyroid fine needle biopsy (FNB) specimens with indeterminate cytology, and to assess the correlation of the type of genetic changes with clinical features and follow-up results in the target thyroid nodule. Methods: Between February 2015 and September 2017, 388 consecutive FNBs with indeterminate cytology were evaluated for TSHR mutations and NIS gene overexpression using ThyroSeqV.2 next-generation sequencing (NGS) panel. Medical records were reviewed for target nodules. Results: Among 388 indeterminate FNBs, TSHR mutations and/or NIS overexpression were detected in 25 (6.4%) nodules. Ten nodules (2.6%) harbored TSHR mutations only, 7 nodules (1.8%) over-expressed NIS gene only, and 8 nodules (2.1%) had both alterations. The TSHR mutations were located in codons 281-640, with codon 453 being the most frequently affected. The allelic frequency of the mutated TSHR ranged from 6% to 36%. One nodule with NIS overexpression was simultaneously detected EIF1AX mutation and GNAS mutation. Nodules with TSHR mutations and/or NIS overexpression presented hyperfunctioning (n=4), hypofunctioning (n=5) and isofunctioning (n=3) on the available thyroid scintigraphies. Eight cases accompanied with hyperthyroidism in which only 1 was caused by the target nodule. Evidence of co-existing autoimmune thyroid disease (AITD) and multinodular goiter were found in 52% and 52% of cases, respectively. Seven nodules underwent surgeries and all were benign on final pathology. None of 9 nodules with follow-up by ultrasound (3m~ 33m, median 12m) showed grow in size. Conclusions: TSHR mutations and/or NIS overexpression can be detected in pre-operative FNB specimens using the NGS approach. These genetic alterations occurred in 6.4% thyroid nodules in this consecutive series with indeterminate cytology. They present not only in hyperfunctioning nodules but also in hypo- or iso-functional nodules, indicating their prevalence may be higher than previously expected. Co-existing AITD was common in cases with these molecular alterations. None of our patients with TSHR mutations and/or NIS overexpression manifested malignant outcomes. How to use these two molecular markers in thyroid FNBs to guide our clinical practice warrants further investigation.